2020
DOI: 10.3389/fenrg.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Treatment of Wood Vinegar via Microbial Electrolysis Cell With the Anode of Different Pyrolysis Biochars

Abstract: Microbial electrolysis cell (MEC) has emerged as the promising technology for COD removal as well as bioenergy recovery during the treatment of bio-refractory wastewaters. This study mainly focused on wood vinegar (the by-product from biomass pyrolysis) treatment via MEC technology with two typical biochars (coconut shell biochar and shrub biochar) as the carriers of microorganisms in anode chamber. Results indicated that MECs with coconut shell biochar had an obvious beneficial effect for treating wood vinega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…TDS content represents the amount of inorganic salt and little organic substances dissolved in a solution. In this study, the TDS content of PA was 1.42 g/L, which was considerably lower than that reported by Shen et al [35]. They showed that carbonation of corn (Zea mays) straw at 600 °C yielded a PA with TDS of 35.0 g/L with a EC value of 2.05 mS cm −1 , which was slightly lower than the ECs of other PA (e.g., 3.54 mS cm −1 [36]).…”
Section: Chemical Qualities and Antioxidant Activitiescontrasting
confidence: 81%
See 1 more Smart Citation
“…TDS content represents the amount of inorganic salt and little organic substances dissolved in a solution. In this study, the TDS content of PA was 1.42 g/L, which was considerably lower than that reported by Shen et al [35]. They showed that carbonation of corn (Zea mays) straw at 600 °C yielded a PA with TDS of 35.0 g/L with a EC value of 2.05 mS cm −1 , which was slightly lower than the ECs of other PA (e.g., 3.54 mS cm −1 [36]).…”
Section: Chemical Qualities and Antioxidant Activitiescontrasting
confidence: 81%
“…Also, Ca content in the white pine PA was 100 mg/L which was higher than Durian PA (14.72 mg/L) produced at 550 °C [72] and mangrove wood (8.82 mg/L) [71]. Conversely, the Ca content was lower when compared to other PAs produced from corn straw (276 mg/L) [35] and oak (375.88 mg/L) [70]. Zn content in this study was 10 mg/L which was higher than PA derived from fruitwood (5.5 mg/L) [36] and mangrove wood PA [71], but lower than PA obtained from oak PA (16.71 mg/L) [70] and Durian PA (36.52-42.71 mg/L) produced at pyrolysis temperature between 350 and 550 °C [72].…”
Section: Mineral Element Contentmentioning
confidence: 99%
“…Among the pyrolysis products, wood vinegar makes up more than 20% of the yield. This means that after treatment, 1000 kg of feedstock will yield over 200 kg of wood vinegar [94]. A schematic diagram of wood pyrolysis for vinegar production is shown in Figure 3.…”
Section: Waste To Vinegar Productionmentioning
confidence: 99%
“…Like other biostimulants, PA cannot be de ned as a fertilizer since it might not supply direct nutrients to plants but can be treated as an additive fertilizer which facilitates nutrient uptake via stimulation of metabolic and biochemical processes in plants and soils 34,35 . It was demonstrated that co-application of PA with other soil amendments including manure 35,36 , biochar 37 and compost 35,38 synergistically improves growth and productivity of crops. Nevertheless, studies on biostimulatory effect of foliar PA application in combination with varying fertilizer regimes on greenhouse tomato yield and fruit quality are limited.…”
Section: Introductionmentioning
confidence: 99%